Functional Properties and Microbiological Stability of Fatty Acid Methyl Esters (FAME) under Different Storage Conditions - Małgorzata Hawrot-Paw; Adam Koniuszy; Paweł Sędłak; Daria Seń (Energies, 2020)
Biofuels used as biocomponents for transport fuels should meet quality requirements. Their properties have a significant impact on the proper functioning of the engine supply system and the wear of its components. Changes in the performance of biofuel functionality may already occur during storage. Therefore, the present study aimed to evaluate changes in selected rheological and tribological parameters of higher fatty acid esters depending on the time and method of their storage by considering different types of substrates used for their production. The presence of possible microbiological contamination, which may affect the examined parameters of biofuels, was also analyzed. The dynamic viscosity of the biofuels tested changed depending on the substrate used. The biofuel produced from waste oil had the highest viscosity. Tribological studies show that both the linear wear of samples and the friction moment were higher after the storage period. The acid number of the esters did not exceed the permissible value recommended by the standard. The type of raw material used for the production of biodiesel and the conditions of its storage affected biodeterioration, proved by the growth of microorganisms. The highest number of microorganisms was recorded in biofuels prepared from waste oil.